ENSURING COMPETITION IN CANADA'S FINANCIAL SERVICES SECTOR - contributors of the Insurance Brokers Association of Canada, Various (Assurances)

(untitled) (HEC Montréal, 1998)
The Minister of Finance and the Secretary of State (International Financial Institutions) announced the creation of the Task Force on the Future of the Canadian Financial Services Sector to undertake a comprehensive review of what needs to be done to ensure that the financial services sector remains strong and dynamic. In its Discussion Paper released in June 1997 the Task Force listed 49 areas of study in preparation for its final report expected in the fall of 1998. It is an ambitious study plan, one that will require some form of order and priority if it is to set the tone for the next review of federal financial services sector legislation scheduled for 2002. The Insurance Brokers Association of Canada (IBAC) was pleased to respond to the government's initiative by presenting a submission reflecting the views of Canada's independent property and casualty insurance brokers. We thanks the IBAC for its kind authorization to publish it in this issue.